Tracing the sources of noble gases for helium prospectivity in the Western Canada Sedimentary Basin - Stuart M.V. Gilfillan; Emma Martin-Roberts; Nicholas Utting; Rachel Utley; Kirk Osadetz; Don Lawton (Chemical Geology, 2026)

Halite formations of Canada for clean energy storage (hydrogen, CAES): A geologic review - Pavel Kabanov; Nicolas Pinet; Frank Brunton; Omid Haeri Ardakani; Christine Deblonde; Keith Dewing; Peter Giles; Paul Durling; Marty Henning; Nicholas Utting (Earth-Science Reviews, 2026)

Potential impacts of diluted bitumen and conventional crude oil leaks occurring above the water table - Nicholas Utting; Jason M. E. Ahad; James Brydie; Alireza Jafari; Craig McMullen; Lisa Duffin (Hydrogeology Journal, 2026)
The production of bitumen in Canada has increased in recent years. In this study, laboratory experiments were conducted to simulate the potential water quality impacts of a leak of diluted bitumen from a pipeline in comparison with a leak of conventional crude oil to improve the understanding of how these hydrocarbons may impact groundwater. Experimental leakage simulations were conducted using groundwater simulation tanks with oil injected above the water table. Diluted bitumen was injected into the first tank, conventional crude into the second tank, and no oil was injected into the third tank. Effluent samples were tested for inorganic water chemistry and selected organic compounds. Bulk stable carbon isotope ratios were determined for total organic carbon (TOC), and compound-specific isotope analysis was carried out on toluene and benzene. Effluent from the tank injected with conventional crude contained higher concentrations of TOC than the diluted bitumen tank. Benzene, toluene, ethylbenzene, and xylene (BTEX) compounds measured in effluent were detected earlier for conventional crude than diluted bitumen. The results of this study suggest that a spill of diluted bitumen, occurring above the water table, is likely to have less of an impact on groundwater quality compared to a spill of conventional crude under the same environmental setting and conditions, owing to the greater viscosity of the diluted bitumen (and in this case lower concentrations of BTEX), which results in fewer hydrocarbons reaching the water table, thus reducing the opportunity for organic contaminants to dissolve into the aqueous phase.

Enhanced hydrogeochemical baseline of a CO2 injection facility in southern Alberta, Canada - Nicholas Utting; Kirk G. Osadetz; Bernhard Mayer; Tiago Morais; Stuart M.V. Gilfillan; Michael Nightingale; Thomas Darrah; Emma Martin-Roberts; Don Lawton (International Journal of Greenhouse Gas Control, 2026)

Spatial and temporal water chemistry variations of hydraulic fracturing flowback and produced waters from the Duvernay Formation - Xiaomeng Wang; Nicholas Utting; Michael S. Reid; Chunqing Jiang; Daniel S. Alessi; Jun Han; Lisa Duffin; Chenxing Sun (Applied Geochemistry, 2023)

Understanding the evolution of oil sands tailings deposits using tritium-helium dating and noble gases - Nicholas Utting; Jean S. Birks; Thomas H. Darrah (Applied Geochemistry, 2023)

Noble gas and isotope geochemistry in western Canadian Arctic watersheds: tracing groundwater recharge in permafrost terrain - Nicholas Utting; Bernard Lauriol; Neil Mochnacz; Werner Aeschbach-Hertig; Ian Clark (Hydrogeology Journal, 2013)